Yağlı Isıl İşlem Görmüş Sarıçam Odunlarında Koruyucu Katmanın Yapışma ve Sertlik Özellikleri - Kesi̇k, Hacı; Vurdu, Hasan; Çağatay, Kubulay; Özkan, Osman; Öncel, Mustafa (Kastamonu University, 2015)
Wood is a preferred important material due to having many advantages for many uses. However, wood is degraded by time under the effects of biotic and abiotic factors. Therefore, wood should be protected from fungi, insects and other climate factors. Among these, heat treatment methods increase the durability of wood properties. Especially, oil heat treatment improves the dimensional stability and color stability in a positive direction. Thus, wood can be used for garden furniture or siding. In this study, water based varnish and paint were applied on oil heat treated scots pine (Pinus sylvestris L.) wood. Effects of oil heat treatment on adhesion strength and hardness of varnish and paint films were determined. Results showed that hardness of varnish layers (38) on oil heat treated scots pine wood is higher than paint layers (25.6)
Keywords: Yağlı ısıl işlem; Su bazlı vernik; Su bazlı boya; Yapışma direnci; Sertlik; Oil heat treatment; Water based varnish; Paint; Adhesion strength; Hardness; 15. Life on land